A formação de professores em educação física e sua relação com o mundo da vida - Silva, Marcio Salles da (2008)
The present study had the purpose of analyzing the historical formation of three academics enrolled in the discipline Physical Education Laboratory II of the second semester of the course of Degree in Physical Education within the representations of the world of life that legitimate the choice for the course and the use of the reflection about the sport in the school together with the influences on the process of professors formation. The methodological choice had its bases on the qualitative model and the assumed form (type) was the case study which had as subject of study three academics of the second semester of the course of Degree in Physical Education of UFSM. We have applied the critical analysis of discourse in order to interpret the information and the critical ethnography for the orientation in the research field of the referred discipline. The research was composed by four stages: 1) ethnographic analyses have been developed through the evidenced thematic after the transcription of the five recorded classes and then they were selected by the similarity of the argumentations during the meetings; 2) the analysis of the life historical of the three academics selected in the ethnography to identify facts and situations relevant to the human movement; the documental analysis of the Pedagogical Politic Project of the course of Degree in Physical Education of UFSM, introduced in 2005, with the purpose of knowing the structure and organization of the disciplines offered by the course during the two first semesters; 4) a collective interview with the three academics in the end of the referred discipline aiming at to provide reflexive discussions by applying the thematic developed on it. We believe that the academics of the course of professors formation in Physical Education are in a continuous process of construction of the identity of learning and teaching that has been experienced during the basic teaching, does not cease from the beginning to the end of the University, goes beyond teaching in the schools, and remains unfinished. We understand that in the course of Degree of the CEFD/UFSM, the thematic transformation of sports and/or the sports and their transformations must has its bases on the objectives of the whole disciplines that address the knowledge about the teaching of sports in spite of being individual or collective. The continuous process of professors formation in the Degree in Physical Education occur through the communicative actions in which we both change and we are changed within a social and cultural cognitive perspective together with our historical formation. We construct ourselves as professionals of education in a commitment with the movement of self-reflection in the critic to the systemic elements that continuously invade the world of life. Keywords: Degree in Physical Education; World of